“IMPLEMENTASI PENDIDIKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB DALAM MENGATASI RENDAHNYA KEDISIPLINAN SISWA SEKOLAH DASAR” - Sri Hartati; Masniar, Dr Hapni Laila Siregar,M.A (STKIP Subang, 2026)
This research seeks to outline the execution of character education that focuses on discipline and responsibility to address the issue of inadequate student discipline in elementary schools. The study employed a qualitative descriptive methodology, engaging classroom teachers and students as participants. Data were gathered through observation, interviews, and documentation to provide a thorough understanding of student behavior and the methods utilized by teachers in character development. The findings indicated that the values of discipline and responsibility were implemented through habituation, teacher modeling, reinforcement of classroom rules, and reflective activities. The process of internalizing character values was enhanced through reward systems, mutual agreements, and consistent role modeling by teachers. Furthermore, the study demonstrated that the discipline and responsibility initiatives positively influenced student behavior, especially in terms of punctuality, task completion, and adherence to school regulations. The implications of this research underscore the significance of collaboration among teachers, parents, and schools in fostering a culture of discipline and responsibility among elementary school students.